Women's autonomy and utilization of maternal health care services in a community of Morang district. - Dahal, Tulasha (2021)
EXECUTIVE SUMMARY: This study report was prepared based on the findings Women's autonomy and maternal health care utilization in a community of Morang district. Descriptive Cross Sectional research design was used to identify the level of women's autonomy and maternal health care utilization among the mothers who have at least one child having under 12 months' age and to find out the association of selected demographic variables and maternal health care utilization and level of women's autonomy and maternal health care utilization. the data was collected from April 20 to July 20 The sample size of the study was 318 married women having at least one child under 12 month of age. The report is divided into four major sections; introduction, research methodology, findings of the study, discussion and conclusion. The introduction section begins with a broader international context to the local context and tried to find the research gap. It also describes the problem, rational for the study, significance of the study and the objectives of the study. The second section is the research methodology, it explains about the research design, sampling technique, sample size, ethical consideration etc. Similarly, the fourth section demonstrates the findings of the study in table with illustration, includes demographic characteristics of the study, Women's autonomy and maternal health care utilization related characteristics and the association of selective demographic variables with utilization maternal health care and women's autonomy level and utilization of maternal health care. The last or fourth section related to the discussion, conclusion, recommendations and limitations of the study. The present study concluded that one third of respondents had high level of autonomy, maternal health service utilization is very low. Literate women had high level of utilization than illiterate. PREFACE Maternal health care refers to the health care that a woman receives during pregnancy, childbirth and postnatal period. Utilization of above all service or care from skilled health worker is crucial for the wellbeing of a mother and new born baby. Ninety-four percent of maternal deaths occur in low and middle-income countries. Due to various interventions in maternal health care services, maternal death has been halved worldwide between 1990 and 2010 but it is still unacceptably high in many low- and middle-income countries. Literatures have shown that Women's autonomy plays even vital role for the utilization of health care services. The objective of the study is to find out women's autonomy and maternal health care utilization in a community of Morang district. Descriptive Cross-sectional study was conducted in the Gramthan Rural municipality (Gaupalika) which is located at Morang district. Study population was married women having at least one child under 12 month of age. Non probability purposive sampling technique was used to collect data with Semi- structured interview schedule. Out of 318 women 36.5% had high level of autonomy and maternal health service was utilized by 29.2% . In bivariate analysis, women's high level of autonomy were 2.033 times higher utilization of maternal health services than women's with low autonomy. (p-value 0.005, CI 1.240-3.334). Likewise, utilization of maternal health services were 0.129 and 0453 times higher among primary and secondary level than illiterate (p-value 0.000 and 0.006, CI 0.42-0.397, 0.256-0.800). Respondents with unemployment, 0.528 times higher utilization of maternal health services than employment (p-value 0.011, CI 0.322-0.866). Ethnicity was also associated with utilization of maternal health services with odds of 2.689 (p-value 0.005, CI 1.3465.374). In multivariate analysis education remained associated with utilization of maternal health services (p-value 0.004, 0.015, 95% CI 1.830-23.342, 1.197-5.184). It was found that respondents with primary and secondary level education were 65% and 24% more utilized maternal health services than illiterate. Occupation also remained associated, with odds ratio of 2.121(p-value 0.010,95% CI 1.200-3.748) for employment, the respondents who were unemployed were 2.121 times high utilized maternal health service than employed. Based on findings it is concluded that one third of respondents had high level of autonomy, maternal health service utilization is very low. Literate women had high level of utilization than illiterate. Key Words: Autonomy, Maternal health care utilization.